High OX-40 expression in the tumor immune infiltrate is a favorable prognostic factor of overall survival in non-small cell lung cancer. Issue 1 (16th December 2019) - Massarelli, Erminia; Lam, Vincent K.; Parra, Edwin R.; Rodriguez-Canales, Jaime; Behrens, Carmen; Diao, Lixia; Wang, Jing; Blando, Jorge; Byers, Lauren A.; Yanamandra, Niranjan; Brett, Sara; Morley, Peter; et al.
Abstract : Introduction: OX-40 co-stimulatory signaling plays a role in mounting anti-tumor immune responses and clinical trials targeting this pathway are ongoing. However, the association of with OX-40 protein expression with clinical outcomes and pathological features in non-small cell lung cancer (NSCLC) are largely unknown. Methods: Surgically-resected stage I-III NSCLC specimens ( N = 100) were stained by immunohistochemistry (IHC) for the following immune markers: OX-40, PD-L1, PD-1, CD3, CD4, CD8, CD45RO, CD57, CD68, FOXP3, granzyme B, and ICOS. Immune-related markers mRNA expression were also assessed. We evaluated the association of OX-40 levels with major clinicopathologic variables, including molecular driver mutations. Results: OX-40 IHC expression was observed in all tested tumors, predominantly localized in the membrane of the tumor immune infiltrate, and was not associated with a specific clinicopathologic or molecular subtype. High OX-40 expression levels measured by IHC median score were associated with better overall survival (OS) ( p = 0.002), independent of CD3/CD8, PD-L1, and ICOS expression. High OX-40 IHC score was associated with increased expression of immune-related genes such as CD3, IFN-gamma, ICOS, CD8, CXCL9, CXCL10, CCL5, granzyme K. Conclusions: High OX-40 IHC expression in the tumor immune infiltrate is associated with favorable prognosis and increased levels of immune-related genes including IFN-gamma in patients with surgically resected stage I-III NSCLC. Its prognostic utility is independent of PD-L1 and other common markers of immune activation. High OX-40 expression potentially identifies a unique subgroup of NSCLC that may benefit from co-stimulation with OX-40 agonist antibodies and potentially enhance the efficacy of existing immune checkpoint therapies.